Concept, nature and history of arbitrary crime (Eurasian Scientific Herald, 2023)
This scientific article describes the history and understanding of the origin of arbitrary crime not only in ancient times, but also in the Middle Ages and modern times. In addition, the analysis of criminal legal norms related to arbitrariness in the Republic of Uzbekistan is briefly presented.Qadimgi jamiyatlarda dastlabki huquqiy tizimlar.